2022
DOI: 10.1029/2021ja030136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Magnetospheric Plasma Interaction and Solar Illumination on Ion Sputtering of Europa’s Surface Ice

Abstract: The icy moon Europa (radius R E = 1,560.8 km) is the smallest of the four Galilean moons of Jupiter, and possesses one of the youngest surfaces of any solar system object (about 50 million years, e.g., Bierhaus et al., 2009). The youth of Europa's surface is the result of continuous resurfacing processes, such as past tectonic activity (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(86 citation statements)
references
References 125 publications
(555 reference statements)
4
75
2
Order By: Relevance
“…In addition, Addison et al. (2022) also observed an increase in the H2O ${\text{H}}_{\text{2}}\text{O}$ sputtering rate and a preferential emission of H2O ${\text{H}}_{\text{2}}\text{O}$ molecules near the upstream apex, in agreement with the findings of Roth (2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, Addison et al. (2022) also observed an increase in the H2O ${\text{H}}_{\text{2}}\text{O}$ sputtering rate and a preferential emission of H2O ${\text{H}}_{\text{2}}\text{O}$ molecules near the upstream apex, in agreement with the findings of Roth (2021).…”
Section: Discussionsupporting
confidence: 75%
“…Roth (2021) speculated that sputtering and secondary sublimation might be the origin of the detected stable H 2 O atmosphere, in line with the results of Teolis et al (2017). In addition, Addison et al (2022) also observed an increase in the 𝐴𝐴 H2O sputtering rate and a preferential emission of 𝐴𝐴 H2O molecules near the upstream apex, in agreement with the findings of Roth (2021).…”
Section: Location Of the Stable H 2 Osupporting
confidence: 81%
“…By averaging over a full synodic period we then constrain the average surface erosion patterns associated with electron bombardment over geologic timescales. Combination of our results with those obtained by Addison et al (2021Addison et al ( , 2022 for magnetospheric ion precipitation allows us to determine the relative contributions of energetic ions and electrons to exosphere generation and surface modification at Europa. The paper is structured as follows.…”
mentioning
confidence: 66%
“…Although the average dominant charge state of energetic oxygen ions (O 1+ vs. O 2+ ) and sulfur ions (S 2+ vs. S 3+ ) near Callisto is under debate (cf., e.g., results presented in Bagenal et al., 2016; Clark et al., 2016, 2020; Collier & Hamilton, 1995; Cooper et al., 2001; Keppler & Krupp, 1996), changing their charge state by one would likely only generate a minor change to the ion flux patterns (see Addison et al., 2021; Liuzzo et al., 2019b). In addition, the use of O 2+ and S 3+ in our model facilitates a straightforward comparison with previous studies of energetic particle dynamics near the icy Galilean moons (e.g., Addison et al., 2021, 2022; Liuzzo et al., 2019a, 2019b, 2020; Plainaki et al., 2015; Poppe et al., 2018).…”
Section: Modeling Energetic Particles Near Callistomentioning
confidence: 86%
“…To solve for the dynamics of energetic ions and electrons as they precipitate onto Callisto's atmosphere, we use the Galilean Energetics Tracing Model (GENTOo; Liuzzo et al, 2019aLiuzzo et al, , 2019b. GENTOo has been used to study energetic particle dynamics near each of the icy Galilean moons (Addison et al, 2021(Addison et al, , 2022Breer et al, 2019, Liuzzo et al, 2019a, 2019b, so only a brief discussion of the model is provided here. GENTOo imports the locally perturbed electromagnetic fields near Callisto as calculated by the AIKEF hybrid model and solves the relativistic Lorentz force equation to calculate the dynamics of energetic test particles using the approach introduced by Vay (2008), which applies a second-order leapfrog solver to advance the particles within the simulation.…”
Section: Tracing Energetic Particle Dynamics: the Gentoo Modelmentioning
confidence: 99%